Soda shop surprise - St. Pierre, Stephenie (ABDO & daughters, 1991)
Midge calls on Barbie for help with the grand opening of her soda shop and then breaks her leg, leaving Barbie holding the soda straws!
64951
Keywords: Dolls; Friendship